GEOPHYSICAL METHODS AND THE PROBLEM OF UNCONVENTIONAL NATURAL GAS SOURCES DETECTION - Lukin, A.Ye. (Institute of Geological Sciences, NAS of Ukraine, 2014)
Advantageous developing of non-traditional sources of natural gas in North-American continent marks the beginning of new stage of global fuel-energetic complex. It poses new problems before the petroleum geophysics. Among them the most important problem is prediction and detection of «sweet spots» – dilatancy «pillows» with increased random fracturing caused by suction into the most hydrophobizated segments of appropriate formations. This stage offers great prospects of the application of passive seismic prospecting (emission tomography, Acoustic Low-Frequency Prospecting – ALFP), analysis of spontaneous electromagnetic emission, also γ-spectrometry and different kinds of emanation surveys.